Neuro fuzzy model to represent the coffee berry borer expansion at Colombian coffee fields - Bazurto Gomez, Nychol; Martınez Morales, Carlos Alberto; Espitia Cuchango, Helbert Eduardo (Visión electrónica, 2014)
In this paper, we propose an ANFIS model based that verify their effectiveness compared to real data to determine the coffee berry borer proliferation risk in a colombian context, verifying its effectiveness compared to real data collected by the ICA in a study of the Integrated Management of Broca. As an initial step, four input variables are determined and a fuzzy model (made in another job), including factors were used: temperature, altitude, age and quality of the crop harvesting. A set of 144 rules and 20 times of training, the results were satisfactory and close to the actual infestation level, fulfilling the target of generating information regarding this problem by using engineering techniques